Problems and Challenges of the Internship Program during the pandemic Covid-19: The perspective of Accounting Student in Indonesia - Mimin Widaningsih; Elis Mediawati; Nor Aishah Mohd Ali; Rozaiha Ab. Majid; Salina Abdullah (Universitas Pendidikan Indonesia, 2022)
This study aims to find out the problems and challenges faced by accounting students who carried out internship programs during the Covid-19 pandemic and find solutions to the problems faced. The survey was conducted by distributing questionnaires to 92 accounting students who carried out internship programs in Indonesia. Problems and challenges faced by accounting students carrying out internship programs during the COVID-19 pandemic, including difficulty communicating with colleagues or other staff, experiencing lack of social interaction with supervisors, inadequate infrastructure, difficulty focusing on work due to family commitments, as well as challenges in carrying out tasks assigned by supervisors due to poor internet connection. As one solution that can be implemented is to carry out a mixed internship program.This research was conducted on students majoring in accounting and because research on perceptions would allow for a subjective explanation. This research provides input to students, educational institutions, alumni, professional association institutions, and partner institutions to improve the quality of internships in the accounting department. This research was conducted on accounting students who carried out internships during the COVID-19 pandemic.